Myeloid- and epithelial-derived RELMα contribute to tissue repair following lung helminth infection - Sveiven, Stefanie N.; Kim, Sang Yong; Barrientos, Valeria; Li, Jiang; Jennett, Jennell; Asiedu, Samuel; Anesko, Kyle; Nordgren, Tara M.; Nair, Meera G. (Frontiers in Parasitology, 2023)
Soil-transmitted helminth (STH) infections impact billions of individuals globally, however, there is a need to clarify the long-term impacts of these infections on pulmonary health due to their transient migration and subsequent damage to the lungs. In mouse models of these infections using Nippostrongylus brasiliensis, lung pathology persists at later timepoints post-single infection. These studies also indicate persistent transcriptional expression of Resistin-Like Molecule α (RELMα), an immunomodulatory protein induced in type 2 immunity and alternatively activated macrophages. Using constitutive and tamoxifen-inducible cell-specific RELMa knockout mouse strains, we identified that epithelial and myeloid-derived RELMα protein remained elevated at day 30 postinfection and altered the immune cell signature and gene expression in lung compartments. Histopathological assessment of alveolar damage revealed a role for RELMα in tissue repair, implicating the importance of sustained RELMα expression for lung recovery from helminth infection. Acellular 3D lung scaffolds were prepared from lungs of WT or RELMaKO naïve or day 30 post N. brasiliensis infection to assess their ability to support epithelial cell growth. N. brasiliensis infection significantly altered the scaffold and impaired epithelial cell growth and metabolic activity, especially in the RELMaKO scaffolds. These findings underscore a need to identify the long-term impacts of helminth infection on human pulmonary disease, particularly as alveolar destruction can develop into chronic obstructive pulmonary disease (COPD), which remains among the top global causes of death. Translation of these findings to related human protein resistin presents therapeutic opportunities in lung repair.